International Corporate Diversification, Market Valuation, and Size- Adjusted Evidence - Errunza, Vihang R.; Senbet, Lemma W. (Journal of Finance, 1984)
Vihang R. Errunza, Lemma W. Senbet, International Corporate Diversification, Market Valuation, and Size- Adjusted Evidence, The Journal of Finance, Vol. 39, No. 3, Papers and Proceedings, Forty-Second Annual Meeting, American Finance Association, San Francisco, CA, December 28-30, 1983 (Jul., 1984), pp. 727-743